Operating Efficiency and Corporate Governance - Dybvig, Philip H. (Institutional Knowledge at Singapore Management University, 2010)
Although empirical studies often use Tobin's Q as a proxy for operating performance, our theoretical framework highlights its ambiguity when evaluating corporate Governance. In particular, capital in the denominator of Tobin's Q is endogenous since entrenched managers can enjoy the quiet life and underinvest (Bertrand and Mullainathan, 2003). Firms that underinvest operate below their firm's profit-maximizing scale. Despite reducing a firm's net present value, underinvestment increases Tobin's Q. Furthermore, strong governance can either decrease Tobin's Q by mitigating underinvestment or increase Tobin's Q by lowering costs. Therefore, the net impact of governance on Tobin's Q is ambiguous. Our framework then provides measures of operating efficiency to assess a firm's scale decisions and cost discipline. These measures capture the benefits of acquisitions that improve scale and lower costs as well as the inefficiencies associated with empire building. Their estimation confirms that underinvestment is responsible for inflating Tobin's Q.